2016
DOI: 10.1371/journal.pone.0147865
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Cruciate Ligament Retention versus Posterior Stabilization for Total Knee Arthroplasty: A Meta-Analysis

Abstract: IntroductionAlthough being debated for many years, the superiority of posterior cruciate-retaining (CR) total knee arthroplasty (TKA) and posterior-stabilized (PS) TKA remains controversial. We compare the knee scores, post-operative knee range of motion (ROM), radiological outcomes about knee kinematic and complications between CR TKA and PS TKA.MethodsLiterature published up to August 2015 was searched in PubMed, Embase and Cochrane databases, and meta-analysis was performed using the software, Review Manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 24 publications
3
55
2
Order By: Relevance
“…32,33 Jiang et al conducted a meta-analysis which showed PS TKA had a better knee flexion postoperatively. 34 Our study also had increased ROM in PS knees compared to CR knees.…”
Section: Cr Versus Pssupporting
confidence: 54%
See 1 more Smart Citation
“…32,33 Jiang et al conducted a meta-analysis which showed PS TKA had a better knee flexion postoperatively. 34 Our study also had increased ROM in PS knees compared to CR knees.…”
Section: Cr Versus Pssupporting
confidence: 54%
“…The patients in the OA category had good postop ROM (p<0.01) ( Figure 1). Mean BMI was 27.23 kg/m 2 (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). Highest BMI 37.34 kg/m 2 and lowest BMI 21.32 kg/m 2 .…”
Section: Resultsmentioning
confidence: 99%
“…As to the choice of surgical technique between CR TKA and PS TKA, a recent meta-analysis collecting 14 Randomized Clinical Trials (RCTs) concluded that there is no clinical-relevant difference between CR TKA and PS TKA in terms of radiological and clinical outcomes, while PS TKA is superior to CR TKA with respect to range of motion (ROM), 13 which might be the result of increased flexion gap and decreased varus angle after PCL sacrifice. One more reason that CR TKA is not preferred is that most of the PCL insertion is likely to be sacrificed fully or partially during preparation of the tibial plateau, 14,15 which will potentially influence the clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…However, generally, no statistical differences in terms of functional and clinical parameters were detected in the previous literature. Nevertheless, the superiority of one of the prosthesis types remains controversial [5759]. Data extracted from the transverse and frontal plane should be interpreted with caution due to its known sources of measurement and modeling issues [29,60].…”
Section: Discussionmentioning
confidence: 99%